(untitled) (Research, Society and Development, 2025)
Introduction: Long COVID refers to the persistence of symptoms even after acute recovery from COVID-19. However, the association of anthropometric and functional variables with Long COVID symptoms requires clarification. Objective: to correlate body weight, body fat, muscle mass, muscle strength and function with a score of Long COVID symptom’s prevalence and severity. Methods: This is a Cross-sectional study. Seventeen adult participants (29.5 ± 7.1 kg/m2) were submitted to body composition, strength and physical function assessments. They answered a Long Covid symptoms prevalence and severity questionnaire. Variables were correlated and participants were compared using the median of the Long Covid symptoms score. Results: muscle mass percentage (r = -0.52) and biceps muscle thickness (r = -0.54) negatively correlated with the symptoms score (P < .05), while body fat (r = 0.56) and BMI (r = 0.59) correlated positively (P < .05). Participants below the median of the symptoms score presented higher muscle mass (30.5 ± 5.5 vs 23.3 ± 3.9%), thickness (26.3 ± 4.2 vs 21.2 ± 4.2mm), relative strength (1.28 ± 0.3 vs 0.96 ± 0.3 AU) and functional performance as per the five times sit-to-stand test (9.7 ± 2.1 vs 12.3 ± 2.4 s), whilst presenting lower body fat percentage (32.0 ± 7.6 vs 45.8 ± 9.4%) and BMI (25.6 ± 4.0 vs 33.1 ± 7.4 kg/m2) compared to those above the median, respectively. Conclusions: participants who have better body composition, greater strength and physical capacity show a lower prevalence and intensity of Long COVID symptoms.